Monocyte Chemotactic Protein 1 in Plasma from Soluble Leishmania Antigen-Stimulated Whole Blood as a Potential Biomarker of the Cellular Immune Response to Leishmania infantum - Ibarra-Meneses, Ana V.; Sanchez, Carmen; Alvar, Jorge; Moreno, Javier; Carrillo, Eugenia (Frontiers in Immunology, 2017)
New biomarkers are needed to identify asymptomatic Leishmania infection as well as immunity following vaccination or treatment. With the aim of finding a robust biomarker to assess an effective cellular immune response, MCP-1 was examined in plasma from soluble Leishmania antigen (SLA)-stimulated whole blood collected from subjects living in a Leishmania infantum-endemic area. MCP-1, expressed 110 times more strongly than IL-2, identified 87.5% of asymptomatic subjects and verified some asymptomatic subjects close to the cut-off. MCP-1 was also significantly elevated in all patients cured of VL, unlike IL-2, indicating the specific memory response generated against Leishmania. These results show MCP-1 to be a robust candidate biomarker of immunity that could be used as a marker of cure and to both select and follow the population in vaccine Phase I-III human clinical trials with developed rapid, easy-to-use field tools.